FAKTOR-FAKTOR YANG MEMPENGARUHI MARGIN PEMASARAN SAPI POTONG DAN DAGING SAPI DI KABUPATEN ACEH BESAR - Hendra Koesmara; Sudi Nurtini; I Gede Suparta Budisatria (Faculty of Animal Science, Universitas Gadjah Mada, 2015)
This research identified the forms of share market, to calculate the price received by farmers and middlemen, and analyze marketing margins of beef cattle market. This research was conducted in June to August 2011, in Aceh Besar regency of Aceh province. The method used in this study was a survey method and field direct observations and interviews using questionnaires to farmers, middlemen (mugge) and meat traders respondent. The number of samples were 420 respondents, including 270 respondents of livestock farmers,105 respondents of middlemen (mugee) and 45 respondents of meat traders (final consumer)from the three districts. This study used regression analysis to determine the effect of variables simultaneously observed the marketing margin. The results showed there were 2 channel marketings, channel marketing I of farmers to the final consumer through two market participants were mugee and meat traders,while the marketing channel II from farmers to consumers through one market participants that was meat traders. In marketing channels I mugee get income share 24.89% with 10.38% share of the cost, while the meat traders got incomeshare 47.70% with 17.03% share of the cost. In marketing channels II meat tradersgot income share 83.00% with17.00% share of the cost. In marketing channels I mugee marketing margin of Rp1,026,293.10/head and the meat traders of Rp1,883,045.98/head, while the meat traders of Rp2,944,838.00/head. The coefficient ofdetermination (R2) equalto 0.337321, which means cattle marketing margin could be explained jointly by 33.73% by the marketing costs, the price at the farmer level and the number of middlemen. The test results of the marketing costs (x1) significantly (P<0.05) on the marketing margin, the price at the farmer level (x2) was highly significant (P<0.01) on the marketing margin and the number of middlemen (x3) didnot affect the marketing margin.(Keywords: Cattle, District of Aceh Besar, Market share, Marketing margin)